CULTURE OF CORRECT USE OF THE INTERNET - Sotvoldiyeva Latofatxon Iqboljon qizi,; Fakhriddin Urinboevich Toshboltaev, (Ustozlar uchun, 2025)
this article explores the importance of cultivating a culture of responsible internet use is explored. It emphasizes the necessity for users to engage with digital content thoughtfully and critically. The author discusses the implications of misinformation, the role of social media in shaping public perception, and the ethical considerations surrounding online behaviors. Furthermore, the article advocates for digital literacy as an essential skill for navigating the complexities of the internet. By promoting awareness and education, it aims to empower individuals to make informed decisions, promote respectful communication, and contribute positively to the online community. This piece serves as a call to action for readers to reflect on their internet habits and foster a more constructive and respectful digital environment.